TRANSPORTASI PUBLIK DAN AKSESBILITAS MASYARAKAT PERKOTAAN - Siti Aminah (Jurnal Teknik Sipil, 2018)
Mass  or  public  transportation  system  is  not  yet  fully  accessible  by  the  public.  The  problem  is  not  only related to a fare matter, but is also due to the continuing development of mass transportation system that does  not  meet  the  publics’  real  need  of  mass  transportation.  In  principle,  public  transportation  should openly  allow  all  groups  with  the  society  to  have  access  for  it;  it  should  especially  provide  fairness guarantee for the poor.